Pengembangan E-Asesmen mini riset terintegrasi kecakapan Abad 21 bagi mahasiswa calon guru - Rahma Widiantie; Ina setiawati; Edi Junaedi; Sifa Pajar Amanah (Postgraduate, University of Mataram, 2025)
The E-Assessment is designed by lecturers as an evaluation instrument for prospective teachers conducting mini-research to support 21st-century skills. The research method used is Research and Development (R&D) with the ADDIE research design. The research sample consists of 50 students enrolled in the Biology Education FKIP Universitas Kuningan. Data collection was conducted through observations to identify problems and assessment needs, questionnaires for expert validation, and feedback from lecturers as users.The E-Assessment was developed using Microsoft Excel and iSpring Suite Maker, featuring a mini-research task on Endocrinology learning, a rubric for assessing 21st-century skills indicators, and cognitive questions. The results of media expert validation indicated that the product is highly feasible (89%), evaluation experts rated it as very feasible (91%), and subject matter experts rated it as very feasible (88%). Based on lecturer responses, the product is practical and effective for use (81%), while the achievement of 21st-century skills using the developed E-Assessment is 87.54%. This indicates an improvement in the 21st-century skills of students through mini-research assessed using the developed E-Assessment. Based on these results, it can be concluded that the developed product can serve as an alternative digital-based authentic assessment that lecturers can use to evaluate students' 21st-century skills.